Agile Delphi methodology: A case study on how technology impacts burnout syndrome in the post-pandemic era - Medina-Dominguez, Fuensanta; Sanchez-Segura, Maria-Isabel; de Amescua-Seco, Antonio; Dugarte-Peña, Germán-Lenin; Villalba Arranz, Santiago (Frontiers in Public Health, 2023)
The post-pandemic era has changed many habits in different areas of our lives. One is the exponential growth in the use of technology to perform work activities. At the same time, there has been a very marked increase in burnout syndrome. Is this a coincidence? Could they be two interconnected developments? What if they were? Can we use technology to mitigate this syndrome? This article presents the methodology Agile Delphi (MAD), an evolved version of the Delphi method, adapted to the needs of today's society. MAD has been used in a specific case study to drive occupational health and safety (OHS) experts to reach a consensus on what technological and non-technological factors could be causing the burnout syndrome suffered by workers in the post-pandemic era. This paper formally presents MAD and describes the stages enacted to run Delphi experiments agilely. MAD is more efficient than the traditional Delphi methodology, reducing the time taken to reach consensus and increasing the quality of the resulting products. OHS experts identified factors that affect and cause an increase in burnout syndrome, as well as mechanisms to mitigate their effects. The next step is to evaluate whether, as the experts predict, burnout syndrome decreases with the mechanisms identified in this case study.